Formation of Sn filled CNTs nanocomposite: Study of their magnetic, dielectric properties and enhanced microwave absorption performance at gigahertz frequencies. Issue 15 (1st August 2022) - Wang, Dongxing; Saleem, Muhammad Farooq; Javid, Muhammad; Qu, Xinghao; Farid, Amjad; Irfan, Muhammad; Xu, Xiaohui; Dong, Xinglong
Abstract: The Simplistic formation, advantageous configuration, non-colossal magnetoresistance and broadband absorption are important parameters for microwave absorbent materials. In this study, a core-shell nanocomposite comprising of Sn-filled carbon nanotubes (Sn/CNTs) was prepared by arc discharge method. The microstructure, morphology and surface composition of Sn/CNTs-based core-shell nanocomposites were characterized in detail. Sn/CNTs nanocomposite showed a magnetic signal due to the broken bonds and defects at interfaces in Sn/CNTs. The weak ferromagnetism was found to be helpful in improving magnetic permeability in the Sn/CNTs which confirms its role as a magnetic loss material under incident electromagnetic wave. Sn-filled CNTs revealed an appropriate value of dielectric constant, which plays an important role in impedance matching upon incident electromagnetic wave. The composite of Sn-CNTs and paraffin with a 50 wt % loading showed the lowest reflection loss (RL) of −43.87 dB at 10 GHz, with a wide effective absorption band (RL ≤ −10 dB) of 3 GHz in thickness of 2.3 mm. This enhanced performance is attributed to the combined effect of the conduction loss in one-dimensional core-shell architecture, the interfacial loss Sn-CNT interface, the magnetic loss due to defects-induced ferromagnetism in Sn shell, and in the carbon-containing atomic layers of CNTs.